2011
DOI: 10.1177/030089161109700218
|View full text |Cite
|
Sign up to set email alerts
|

Primary Breast Lymphoma Clinically Mimicking Acute Mastitis: A Case Report

Abstract: Extranodal non-Hodgkin lymphoma of the breast is a rare disease. We present a case of primary breast lymphoma with atypical clinical manifestations that looked like acute mastitis. A 46-year-old woman had noted a painful swelling in the right breast for 2 months. The mass had an inflammatory appearance and acute mastitis was the clinical impression. She underwent a core biopsy of the mass, and pathology showed inflammatory changes. The inflammatory mass regressed and recurred during hospitalization, and furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Differentiating breast lymphoma from inflammatory diseases is challenging, especially in patients with a painful breast lump, erythema, or skin thickening [44,45]. Inflammatory breast diseases include infectious mastitis, abscess, or idiopathic granulomatous lobular mastitis.…”
Section: Differential Diagnosis From Other Breast Malignancies and Inmentioning
confidence: 99%
“…Differentiating breast lymphoma from inflammatory diseases is challenging, especially in patients with a painful breast lump, erythema, or skin thickening [44,45]. Inflammatory breast diseases include infectious mastitis, abscess, or idiopathic granulomatous lobular mastitis.…”
Section: Differential Diagnosis From Other Breast Malignancies and Inmentioning
confidence: 99%
“…These are most often cases of pure primary squamous cell carcinoma of the breast [1518] but also primary lymphoma [18, 19] or even lymphoepithelioma-like carcinoma originally presented as an abscess, although it is very rare [20]. Even in breastfeeding an abscess may turn out to be cancer [21].…”
Section: Discussionmentioning
confidence: 99%
“…Primary squamous cell carcinoma of the breast is rare, accounting for less than 0.4% of all cases of breast cancer. (5) There are also reports of primary breast B-cell lymphoma that present with the initial clinical image of breast sepsis -Sun et al (9) and Antoniou et al (10) reported a unilateral and a bilateral case, respectively. The patients in those two reports did not harbour a typical abscess despite the highly inflammatory clinical features of the breast.…”
Section: Discussionmentioning
confidence: 99%